Skin irritability to sodium lauryl sulfate is associated with increased positive patch test reactions - Schwitulla, Judith; Brasch, J.; Löffler, H.; Schnuch, A.; Geier, J.; Uter, Wolfgang (British Journal of Dermatology, 2014)
As previous observations have indicated an inter-relationship between irritant and allergic skin reactions we analysed data of synchronous allergen and sodium lauryl sulfate (SLS) patch tests in terms of a relationship between SLS responsiveness and allergic patch test reactions.To analyse differences in terms of allergen-specific and overall reaction profiles between patients with vs. those without an irritant reaction to SLS.Clinical data of 26 879 patients patch tested from 2008 to 2011 by members of the Information Network of Departments of Dermatology were analysed. After descriptive analyses, including the MOAHLFA index, the positivity ratio and the reaction index, a negative binomial hurdle model was adopted to investigate the correlation between SLS reactivity and positive patch test reactions.Men, patients aged >= 40 years and patients with an occupational dermatitis background were over-represented in the SLS-reactive group. Patients with an irritant reaction to SLS showed a higher proportion of weak positive reactions, as well as more questionable and irritant reactions to contact allergens than patients not reactive to SLS. The risk of an additional positive patch test reaction increased by 22% for SLS-reactive patients compared with those who were SLS negative.The marked association between SLS reactivity and the number of positive reactions in patch test patients may be due to nonspecific increased skin reactivity at the moment of patch testing only. However, increased SLS reactivity could also be due to longer-lasting enhanced skin irritability, which may have promoted (poly-)sensitization. Further studies, for example with longitudinal data on patients repeatedly patch tested with SLS and contact allergens, are necessary.
EVALuna2:5456